P113/O17 Human lymph node stromal cells express self-antigens targeted by anti-citrullinated protein antybodies: role for tolerance induction in rheumathoid arthritis. (March 2019) - Grasso, C; Hähnlein, JS; Nadafi, R; De Jong, TA; Ramwadhdoebe, TH; Semmelink, JF; Gerlag, DM; Tak, PP; Mebius, RE; Safy, M; Maas, M; Catrina, AI; et al.
Abstract : Career situation of first and presenting author: Student for a master or a PhD. Introduction: In rheumatoid arthritis (RA) the cause for loss of tolerance and anti–citrullinated protein antibody (ACPA) production remains unidentified. Mouse studies showed that peripheral tolerance can be maintained through presentation of peripheral tissue antigens (PTAs) by lymph node stromal cells (LNSCs). We hypothesize that deregulation of peripheral tolerance mechanisms mediated by LNSCs might underlie pathogenesis of RA. Here we investigated the expression of PTAs, citrullinated proteins and immunomodulatory molecules by human LNSCs during health and autoimmunity. Methods: LN tissue sections and LNSCs were prepared from freshly collected lymph node needle biopsies obtained from 24 patients with RA, 23 individuals positive for autoantibodies but without clinical apparent disease (RA-risk group) and 14 seronegative healthy controls. Expression of PADI enzymes, citrullinated proteins, DEAF1, AIRE and PTAs was investigated at mRNA and protein level. Expression of immunomodulatory molecules in LNSCs was assessed after stimulation with IFNγ (n=15). Results: Citrinullated proteins, targeted by ACPA, were found in human LN tissue as well as in cultured LNSCs. In addition, we observed the expression of transcription factors AIRE and DEAF1 as well as disease-related PTAs in LNSCs with some PTAs showing a distinct expression pattern in autoimmune LNSCs compared to healthy controls. TGF-β was constitutively expressed by LNSCs while CD86 or IL-10 were not detected. Upon IFNγ stimulation LNSCs upregulated MHC class II, co-stimulatory molecules CD40 and CD80 as well as T cell negative regulators CD274, NOS2 and IDO. Overall, no clear differences between donor groups were observed for these markers with exception of a slightly lower induction of CD40 and NOS2 in RA LNSCs. Conclusions: We present for the first time that human LNSCs express several PTAs and the transcription factors AIRE and DEAF1, driving PTA expression. Additionally, human LNSCs express molecules involved in citrullination, antigen presentation and immunomodulation. Moreover, antigens targeted by ACPAs are present in LN tissue and LNSCs. These data suggest that LNSCs have the machinery to regulate peripheral tolerance. Disclosure of Interest: None declared.